Analysis of consumers' requirements for data/information quality by using HOQ - Keqin Wang; Shurong Tong; Roucoules, L.; Eynard, B. (2008 IEEE International Conference on Industrial Engineering and Engineering Management, 2008)
Data/information quality (DQ/IQ*) has great impact on data consumers' decisions. In order to provide high quality data/information, data consumers' requirements for DQ/IQ have to be analyzed and identified. Right requirement identification is fundamental to data quality control activities including DQ/IQ measurement, evaluation, improvement, etc. Quality function deployment (QFD) and the house of quality (HOQ) are effective tools to translate consumers' requirements into specific DQ dimensions for DQ improvement. This work briefly introduces QFD, HOQ and their constitutive elements. Data consumers are also examined. A methodology of applying HOQ in DQ/IQ, which includes five major steps, is described in details. Then an example of product design information quality is presented. By using the methodology, the weak points of DQ in industrial firms can be identified in the form of DQ dimensions in order to take actions to improve data/information quality.